Physical properties and biocompatibility of UHMWPE-derived materials modified by synchrotron radiation - Bykova, Iuliia; Weinhardt, Venera; Kashkarova, A.; Lebedev, S.; Baumbach, T.; Pichugin, V.; Zaitsev, K.; Khlusov, I. (Journal of materials science, 2014)
The applications of synchrotron radiation (SR) in medical imaging have become of great use, particularly in angiography, bronchography, mammography, computed tomography, and X-ray microscopy. Thanks to recently developed phase contrast imaging techniques non-destructive preclinical testing of low absorbing materials such as polymers has become possible. The focus of the present work is characterization and examination of UHMWPE-derived materials widely used in medicine, before and after their exposure to SR during such testing. Physical properties, such as wettability, surface energy, IR-spectroscopy, roughness, optical microscopy, microhardness measurements of UHMWPE samples were studied before and after SR. The relationship between a growth of UHMWPE surface hydrophilicity after SR and surface colonization by stromal cells was studied in vitro. Obtained results demonstrate that SR may be used as prospective direction to examine bulk (porous) structure of polymer materials and/or to modify polymer surface and volume for tissue engineering.